5-Fluorouracil/Coumarin and 5-Fluorouracil/Chromone Hybrids: Synthesis and Drug-Likeness Modeling - Laura Giraldo-Arroyave; Andrés F. Yepes; Wilson Cardona-Galeano (Molbank, 2024)
A series of 5-fluorouracil/coumarin and 5-fluorouracil/chromone hybrids were synthesized with good yields using click chemistry as the key step. The structures of these compounds and all intermediates were elucidated by spectroscopic analysis. Furthermore, pharmacokinetic and drug-like computations taken together indicated that the novel hybrids have a strong possibility to advance to further biological studies.